Sustainability champions?: Academic identities and sustainability curricula in higher education. Issue 3 (3rd May 2016) - Wood, Bronwyn E.; Cornforth, Sue; Beals, Fiona; Taylor, Mike; Tallon, Rachel
Abstract : Purpose: The purpose of this paper is to explore the experiences of academic staff who are committed to embedding sustainability within tertiary curricula and pedagogy. Design/methodology/approach: The focus of this paper is on a New Zealand university. A survey of staff was undertaken and in-depth interviews conducted with 11 sustainability "champions". A narrative variant of thematic analysis was used to examine the ways these sustainability "champions" made sense of the work they do. Through an analysis of their metaphors and metaphorical language, a sense of the identities that they held as educators of sustainability was gained. Findings: Three types of identities emerged – the sustainability "saviour", "nurturer" and "struggler". These identities reflected the champion's experiences, disciplinary affiliations and pedagogical approaches. Interdisciplinarity emerged as a key tenet and challenge for such sustainability champions. Originality/value: This paper provides rare insights into the experiences, identities and teaching approaches of sustainability champions within higher education. It highlights the need for university-wide conversations and cross-discipline support for such academics.